#ForgetJamesBond: diversity, inclusion and the UK's intelligence agencies. Issue 7 (10th November 2021) - Lomas, Daniel W. B.
ABSTRACT: Diversity and inclusivity remain top priorities for UK intelligence, having been much maligned for the largely white, male stereotype. The Intelligence & Security Committee of Parliament has published a number of reports suggesting that, even in 2018, the UK's agencies were still behind Whitehall. Historically, there have been issues with female, BAME and LGBT representation, with the article placing today's criticism of the agencies in historical context with a particular focus on the period after 1945. The article also examines the position now and the steps taken by the agencies to promote change, suggesting there are grounds for cautious optimism.